LEARNING MEDIA DEVELOPMENT I-SPRING TECHNOLOGY ON THE SUBJECT OF ART AND CULTURE VISUAL ART 2D MATERIALS - Misron Zen Fatro; Edy Tri Sulistyo; Sugeng Nugroho (Universitas Sebelas Maret, 2017)
I-Spring program is a computer application used to create instructional multimedia. This study aims to find out the design of I-Spring technology learning media on cultural arts subjects and its influence on students cognitive development on two-dimensional art material. Research methodology used is research and development (R & D) with research subjects of grade X Batik 2 Surakarta Senior High School. The development of I-Spring technology learning media includes four main stages namely; (1) preliminary research, (2) development design, (3) production, (4) product validation. The result of the research shows that I-Spring teaching media can improve students' cognitive ability in two dimensional art material.